Biocide susceptibilities and biofilm-forming capacities of Acinetobacter baumannii clinical isolates from Malaysia - Muhammad Harith Nor A'shimi; Ahmed Ghazi Alattraqchi; Farahiyah Mohd Rani; Nor Iza A Rahman; Salwani Ismail; Fatimah Haslina Abdullah; Norlela Othman; David W Cleary; Stuart C Clarke; Chew Chieng Yeo (Journal of Infection in Developing Countries)
Introduction. Acinetobacter baumannii is a Gram-negative nosocomial pathogen that has the capacity to develop resistance to all classes of antimicrobial compounds. However, very little is known regarding its susceptibility to biocides (antiseptics and disinfectants) and capacity to form biofilms, particularly for Malaysian isolates.